Effect of salinity (Na2SO4) on stomata, and yield parameters of Indian mustard (Brassica juncea L) var. Goldi - Ruhi Khan; Farha Rehman; Gulafshan; Aabshar Khan (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2020)
Here, our research on effect of increasing different concentrations (0, 4Mm hos/cm, 8Mm hos/cm and 12Mm hos/cm) of salt (Na2SO4) on plant growth ,and yield parameters of Brassica juncea (var. Goldi). After plant growth with salt treatment, identify the number of leaf with untreated plant. Here our experiment was completely randomize design with three replicates. After randomely selected plants start the process of observation of number of stomata in mature leaves on both sides (abaxial and adaxial) at 65 & 75 (DAS). Here, in our experiment determine the number of stomata due to different concentrations of salt (Na2SO4) as compared to control. However, at the maximum concentrations i.e (8Mm hos/cm and 12Mm hos/cm) of salt , stomata become close as compared with control and low level treatment (4Mm hos/cm) . On the other hand after the plant growth, next step of our experiment observation of the yield parameters of Brassica juncea (var. Goldi) at 120 DAS. The strongest reduction of yield parameters was observed in the 12Mm hos/cm treatment. Our result suggested that, due to salinity level stomata become destroy without show any damage on physiological characters.